Systemic Functinal Grammar (SFG) Analysis on Short story Geri, The Forgetful Elephant - Tiara Aulia; Nasution, Rara Difania; Sintia Trinanda; Tampubolon, Jonris (English Lecturers and Teachers Association (ELTA), 2024)
This research aims to analyse current literature in the framework of a systematic linguistic approach for grammars. Using the short story